2017
DOI: 10.15666/aeer/1504_117128
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Crossbreeding Parameters for Growth and Conformation Traits in Nigerian Indigenous and Exotic Pig Breeds

Abstract: Abstract. Information on the crossbreeding parameter estimates involving Nigerian Indigenous pigs and exotic breeds are rare, as well as the best combination for improved growth and conformation traits. A 3×3 diallel cross was conducted among three breeds of pigs -Large White (WW), Landrace (RR) and Nigerian Indigenous pig (NN) breeds. Growth traits measured were body weight at birth (BWB), weaning (BWW at 6 weeks), maturity of 20 weeks (BW20) and average daily gain (ADG up to 20 weeks), while conformation tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…GCA for LS 0, LS 42, and MR 42 of Local breed was similar to that of Flemish Giant, but higher than that of Rex. The breed with the greatest GCA expected would give larger LS (Okoro and Mbajiorgu, 2017). The higher GCA indicated that Local breed would have a larger litter size at birth.…”
Section: Resultsmentioning
confidence: 95%
“…GCA for LS 0, LS 42, and MR 42 of Local breed was similar to that of Flemish Giant, but higher than that of Rex. The breed with the greatest GCA expected would give larger LS (Okoro and Mbajiorgu, 2017). The higher GCA indicated that Local breed would have a larger litter size at birth.…”
Section: Resultsmentioning
confidence: 95%
“…Kurnianto et al, (2010) in analysis of partial diallel cross among Duroc, Yorkshire and Landrace, had observed highest GCA in Duroc breed for traits such as litter size/weight at birth, number of nipples, litter size/weight at weaning, average daily gain before/after weaning and body weight at 42 days of age as compared to Yorkshire and Landrace. Similarly, Okoro and Mbajiorgu (2017b) had also observed significant GCA effects for growth and body weight gain traits up to 20 weeks of age among Large white, Landrace and Nigerian indigenous breeds of pig.…”
Section: Utilization Of Combining Ability Effects From Diallel Crossesmentioning
confidence: 85%
“…length of ear, tail, snout and body, heart girth, snout circumference and height at withers among Indigenous Nigerian (IN), large white (LW) and landrace breeds. However, Okoro and Mbajiorgu (2017b) had reported no such effects for growth and reproductive traits.…”
Section: Utilization Of Reciprocal Effects From Diallel Crossesmentioning
confidence: 98%
See 1 more Smart Citation